Home-Learning Practices in Kenya: Views of Parents and Education Officers - Nyatuka, Benard Omenge (Asian Journal of Education and Training, 2016)
In order for children to acquire meaningful education, families are advised to participate in learning activities at home. Such activities range from monitoring homework, problem-solving to reading with children during leisure time. But home-learning was claimed to receive little attention from key stakeholders among primary schools in Kenya’s Kakamega County. This study therefore, was meant to explore the home-learning practices in the sampled schools. A review of the literature relevant to home-learning as well as interviews were conducted. The interview participants, who were purposively selected, included twelve parents, thirteen Parent Teacher Association (PTA) chairpersons and ten District Quality Assurance and Standards Officers (DQASOs). Guided by interview schedules, semi-structured individual interviews were conducted. The findings were presented in a narrative format backed by verbatim quotations. The findings revealed gaps with respect to the home-learning practices in the county. On this basis, efforts could be combined towards strengthening home-learning so as to improve both children’s academic achievement as well as behaviour.